Certain Results on \((k,μ)\)-Contact Metric Manifold endowed with Concircular Curvature Tensor - Kumar, R. T. Naveen; Reddy, P. Siva Kota; Venkatesha,; Sangeetha, M. (Communications in Mathematics and Applications, 2023)
The purpose of this paper is to study concircular curvature tensor on \((k,μ)\)-contact metric manifold. Here, first we consider \(φ\)-concircularly flat \((k,μ)\)-contact metric manifold. Next, we describe concircularly pseudo-symmetric \((k,μ)\)-contact metric manifold. Later, we study concircularly \(φ\)-recurrent \((k,μ)\)-contact metric manifold. Finally, we provide the three dimensional example for the existence of non-Sasakian concircularly \(φ\)-recurrent \((k,μ)\)-contact metric manifold.